Dissection Flap Fenestration with a Transjugular Intrahepatic Portosystemic Shunt Needle: an Adjuvant Technique in Endovascular Treatment of Post-Dissection Thoraco-Abdominal Aortic Aneurysms - Correia, R (2021)
Introduction: In chronic aortic dissection complicated by aneurysmal degeneration, the absence of spontaneous tears between the true and false lumen at visceral artery level may limit treatment by fenestrated/branched endovascular aneurysm repair (F/BEVAR). The creation of new fenestrations may be required to allow access to the visceral vessels. Technique: In this video, the endovascular treatment of a 70 year old white man with chronic type B aortic dissection complicated by Crawford type II thoraco-abdominal aortic aneurysmal degeneration is presented. The right renal artery had a false lumen origin without nearby visible re-entry tears. He underwent dissection flap fenestration at visceral vessel level using a transjugular intrahepatic portosystemic shunt (TIPS) needle and subsequent dilation with a high pressure balloon. A Zenith TX2 dissection endovascular graft was deployed proximally and extended distally with a Zenith dissection endovascular stent until the fenestration level was reached. In a second stage, a F/BEVAR was performed, with fenestration to the left renal artery and branches to right renal artery, superior mesenteric artery, and coeliac trunk. One year follow up computed tomography angiography showed visceral branch patency and a reduction of the aneurysm sac. Discussion: The chronic dissection flap may be thick and fibrotic, creating a technical challenge for endovascular fenestration. The off label use of a TIPS needle in this procedure created a new fenestration at the desired level and allowed definitive post-dissection treatment of the thoraco-abdominal aneurysm.